2020
DOI: 10.1017/s104795112000133x
|View full text |Cite
|
Sign up to set email alerts
|

Insights into stent implantation for coronary artery lesions caused by Kawasaki disease

Abstract: AbstractFifty years have passed since the first report of Kawasaki disease in 1967, and the prevalence of acute coronary syndrome in Kawasaki disease patients with coronary artery lesions exceeding 40 years old has increased. Primary coronary stent implantation is currently an acceptable method in ischaemic coronary heart disease in adults. However, it is unknown whether the stent implantation is effective or not in this population. As the clue to answer this question, I review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…If the patient is younger, it may be better to avoid an emergency stent implantation except in life-threatening situations requiring rescue. 15 In our institution, the following factors favour selection of PTCRA for treatment: evidence of ischaemia and single-vessel disease rather than multi-vessel disease, and a limitation of burr size confining the procedure to bigger children. However, if re-vascularisation with CABG rather than the target branch is contemplated, a combined therapy would be useful in patients with multi-vessel disease.…”
Section: Discussionmentioning
confidence: 96%
“…If the patient is younger, it may be better to avoid an emergency stent implantation except in life-threatening situations requiring rescue. 15 In our institution, the following factors favour selection of PTCRA for treatment: evidence of ischaemia and single-vessel disease rather than multi-vessel disease, and a limitation of burr size confining the procedure to bigger children. However, if re-vascularisation with CABG rather than the target branch is contemplated, a combined therapy would be useful in patients with multi-vessel disease.…”
Section: Discussionmentioning
confidence: 96%
“…In 2020, Tsuda reviewed 33 patients who underwent stent implantations and reported that late-period adverse effects were found in 19 (68%) of 28 vessels with follow-up angiograms. The rate of being free of adverse effects at three years after the procedure was only 25% ( 14 ).…”
Section: Discussionmentioning
confidence: 99%